2011
DOI: 10.1186/1471-2458-11-671
|View full text |Cite
|
Sign up to set email alerts
|

Diet, physical exercise and cognitive behavioral training as a combined workplace based intervention to reduce body weight and increase physical capacity in health care workers - a randomized controlled trial

Abstract: BackgroundHealth care workers comprise a high-risk workgroup with respect to deterioration and early retirement. There is high prevalence of obesity and many of the workers are overweight. Together, these factors play a significant role in the health-related problems within this sector. The present study evaluates the effects of the first 3-months of a cluster randomized controlled lifestyle intervention among health care workers. The intervention addresses body weight, general health variables, physical capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
141
1
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(162 citation statements)
references
References 47 publications
7
141
1
13
Order By: Relevance
“…These types of exercises are not appropriate for health gains in terms of weight, blood pressure, body fat, and waist circumference [10,21,22]. As expected, there were no significant differences in weight, blood pressure, body fat, and waist circumference across groups.…”
Section: Table 2 (Continued)mentioning
confidence: 73%
See 2 more Smart Citations
“…These types of exercises are not appropriate for health gains in terms of weight, blood pressure, body fat, and waist circumference [10,21,22]. As expected, there were no significant differences in weight, blood pressure, body fat, and waist circumference across groups.…”
Section: Table 2 (Continued)mentioning
confidence: 73%
“…Work-related musculoskeletal disorders are a major cause of disability in working age individuals [10,11]. Several studies have shown that repetitive work can contribute significantly to an increase in musculoskeletal disorders in workers and to absenteeism [7,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there are some well-documented effective initiatives that included diet programs for reducing weight and PA programs for improving physical capacity and reduce musculoskeletal pain among workers [12][13][14][15]. PA interventions improve muscle strength, stretching and postural control such as coordination training which may be particularly relevant for preventing osteoarticular deterioration and musculoskeletal pain in workers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…PA interventions improve muscle strength, stretching and postural control such as coordination training which may be particularly relevant for preventing osteoarticular deterioration and musculoskeletal pain in workers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%